1998
DOI: 10.3109/07357909809115775
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Efficacy of Sargramostim (Yeast-Derived RhuGM-CSF) and Filgrastim (Bacteria-Derived RhuG-CSF) in the Therapeutic Setting of Chemotherapy-Induced Myelosuppression

Abstract: A randomized, double-blind, multicenter study in 181 afebrile cancer patients with ANC levels < 500/microL receiving myelosuppressive chemotherapy was undertaken to compare sargramostim (yeast-derived recombinant human granulocyte-macrophage colony-stimulating factor, RhuGM-CSF) and filgrastim (bacteria-derived recombinant human granulocyte colony-stimulating factor, RhuG-CSF) in the treatment of chemotherapy-induced myelosuppression. Patients received daily subcutaneous (SC) injections of either agent until A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…As would be expected, the current APAC group had the highest IOP (48.5 mm Hg), followed by the previous APAC group (26.0 mm Hg), and the cataract group (13.3 mm Hg) (all P < 0.0167). The median duration before surgery of the current APAC group was 3.0 days (range, 1-7 days), and that of the previous APAC group was 20.0 days (range, 11-30 days; P < 0.001).…”
Section: Demographic and Clinical Characteristics Of The Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…As would be expected, the current APAC group had the highest IOP (48.5 mm Hg), followed by the previous APAC group (26.0 mm Hg), and the cataract group (13.3 mm Hg) (all P < 0.0167). The median duration before surgery of the current APAC group was 3.0 days (range, 1-7 days), and that of the previous APAC group was 20.0 days (range, 11-30 days; P < 0.001).…”
Section: Demographic and Clinical Characteristics Of The Patientsmentioning
confidence: 99%
“…Inflammatory chemokines are produced in high concentrations during infection or injury and determine the migration of inflammatory leukocytes into the damaged area. G-CSF is used to stimulate the survival, proliferation, differentiation, and function of granulocytes, 20 which play an important role in inflammation. Previous studies of inflammatory eye disease 3,21,22 have reported that increased IL-6, IL-8, and MCP-1 levels, in addition to the shifting of the granulocyte stimulating factor from primary GM-CSF to G-CSF, were commonly associated with intraocular inflammation, regardless of disease etiology.…”
Section: Inflammation-related Cytokines In Aqueous Humor In Apacmentioning
confidence: 99%
“…Injection site reactions as well as exacerbation of preexisting inflammatory conditions have similar frequencies between the two. Comparative safety and efficacy data of G-CSF versus GM-CSF are limited and conflicting, and the long-term consequences of maintenance G-CSF or GM-CSF use in the absence of a primary hematological problem are unclear 30-33. For this reason, choice of one agent over the other is generally based on the system's formulary preference.…”
Section: Discussion: Responding To Clozapine-induced Neutropenia and mentioning
confidence: 99%
“…For many patients, not only the cancer, but also the therapy itself undermines their daily activities. In this regard, several anticancer chemotherapies are combined with G-CSF (Filgrastim, commercially traded as Neupogen*, or Pegfilgrastim commercially traded as Neulasta*) to stimulate proliferation and differentiation of granulocytes [20]. This combination is effectively used to enhance the quality of life of patients suffering from cancer [21,22] by restoring the levels of neutrophils in blood [23-25].…”
Section: Discussionmentioning
confidence: 99%
“…This study shows ABQ-48 and NBQ-48 to effectively induce both effects: control of tumor growth and immune modulation to produce G-CSF, among other cytokines. Therefore, ABQ-48 and NBQ-48 could induce tumor-proliferation control with minimal side effects after stimulating proliferation and differentiation of granulocytes [20] and at some degree restoring the levels of neutrophils in blood.…”
Section: Discussionmentioning
confidence: 99%